On the effect of initial stress in a 3D half-space on superimposed harmonic stresses - Özaydin, O (EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2001)
We determine by Fourier transform method, the effect of homogeneous initial stress in a 3D compressible elastic half-space on harmonic stresses superimposed by a surface force when the initial deformation is not finite. We then show that such an initial tension homogenizes amplitude fields to a small extent. (C) 2001 Academie des sciences/Editions scientifiques et medicales Elsevier SAS.
Keywords: vibration; initial stress; half-space; harmonic stress; Fourier transform; GROUND VIBRATION; RECTANGULAR LOAD; VICINITY; Mechanics